2012
DOI: 10.1634/theoncologist.2011-0377
|View full text |Cite
|
Sign up to set email alerts
|

High ERK Protein Expression Levels Correlate with Shorter Survival in Triple-Negative Breast Cancer Patients

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 34 publications
3
79
0
Order By: Relevance
“…The suppression of the MAPK pathway by the MEK inhibitor selumetinib was found to be effective in preventing lung metastasis of TNBC through the reversal of epithelial-mesenchymal transition, as reported in vitro and in vivo [37]. In patients with TNBC, the overexpression of ERK2 was found to indicate a high risk of death [38]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 58%
“…The suppression of the MAPK pathway by the MEK inhibitor selumetinib was found to be effective in preventing lung metastasis of TNBC through the reversal of epithelial-mesenchymal transition, as reported in vitro and in vivo [37]. In patients with TNBC, the overexpression of ERK2 was found to indicate a high risk of death [38]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 58%
“…In TNBCs, these two pathways are known to be activated and are associated with a poor prognosis (38,39). A recent study suggested that a combination regimen with MEK/ERK and PI3K inhibitors might effectively be used to treat basal-like breast cancers (40).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have reported a trend toward higher MAPK signaling in the primary tumors of nodepositive patients than in the primary tumors of nodenegative patients [11]. It was reported recently that the levels of ERK1/2 expression were correlated with shorter survival in triple-negative breast cancer patients [13]. Studies have also shown that the expression of ERK1/2 was higher in breast cancer specimens, compared with control tissues, and was higher in Stage III patients than in Stage I and Stage II patients [14].…”
Section: Introductionmentioning
confidence: 98%